Peran K.H Abdul Halim Dalam Kehidupan Keberagaman Masyarakat Urban dan Multikultural di Desa Bandar Khalifah, Kecamatan Percut Sei Tuan, Sumatera Utara - Gurning, Muhammad Rizky; Daulay, Maraimbang; R, Ryandi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The diversity of the community in Bandar Khalifah Village, Percut Sei Tuan Subdistrict, North Sumatra reflects the social conditions of an urban and multicultural society consisting of various ethnic, religious, and cultural backgrounds. Within this pluralistic reality, there is a potential risk of conflict if it is not grounded in unifying values. One of the key values believed to be capable of maintaining social harmony is the value of tauhid (Islamic monotheism), particularly as formulated by K.H. Abdul Halim. His conception of tauhid not only focuses on theological aspects but also addresses the dimensions of social and communal ethics. This study aims to examine K.H. Abdul Halim’s thought on tauhid and explore its relevance in fostering harmonious social relations within an urban and multicultural society. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with religious leaders, community leaders, and local residents, as well as participatory observation and document analysis. The findings reveal that K.H. Abdul Halim’s teachings on tauhid serve as a strong moral foundation for fostering tolerance, solidarity, and social responsibility. These values have proven to be relevant in strengthening social cohesion and creating harmony in a diverse community life. The study concludes that K.H. Abdul Halim’s thought plays a significant role in shaping the social ethics of a pluralistic society.